The Global Integrated Monetary and Fiscal Model (GIMF) : Theoretical Structure - Laxton, Douglas (IMF Working Papers; Working Paper ;, 2010)
This working paper presents a comprehensive overview of the theoretical structure of the Global Integrated Monetary and Fiscal Model (GIMF), a multi-region dynamic general equilibrium model that is used by the IMF for a variety of tasks including policy analysis, risk analysis, and surveillance.